INTEGRASI NILAI KEARIFAN LOCAL NGAHA AINA NGOHO DALAM PROGRAM PENGUATAN MITIGASI DAN TANGGAP DARURAT BENCANA PADA SATUAN PENDIDIKAN DI KABUPATEN BIMA - Tati Haryati; A. Gafar Hidayat (Universitas Islam Kalimantan Muhammad Arsyad Al-Banjari Banjarmasin, 2024)
The purpose of writing this article is to provide recommendations to educational units in Bima Regency to integrate the value of local wisdom of ngaha aina ngoho as a program to strengthen disaster mitigation and emergency response. As designed by the Ministry of Education and Culture, to create a culture of preparedness, safety and disaster response in schools, this is an effort to provide understanding to teachers and students about appropriate actions in dealing with emergency situations that occur at school, so as to minimize the risk of disasters they face. Several educational units in Bima Regency are prone to flooding. This happens not only because of the high rainfall, but the majority of Bima's population work as farmers and on average during the rainy season they clear the forest to use it as agricultural land. Meanwhile, the Bima people have the local wisdom value ngaha aina ngoho, the simple meaning of which is